Optimization of anthocyanin and phenolic extraction from butterfly pea (Clitoria ternatea) flowers using response surface methodology - Izon, Jerome Ivan H. (College of Home Economics, University of the Philippines Diliman, 2021)
Response surface methodology was utilized to determine the optimal process variables for the anthocyanin and phenolic extraction of butterfly pea (Clitoria ternatea) flowers. Using the Box-Behnken design, seventeen runs containing varying temperture 3(0-80°C), solid to liquid ratio (1:5-1:50), and time (5-40 mins) were generated to test for the amount of total anthocyanin and phenolic content in the aqueous extract of butterfly pea. Both responses were measured using different spectrophotometric techniques. Response surface models for both were obtained and tested for analysis of variance (ANOVA). Results showed that all the models were significant (p<0.05) thus, optimal extraction parameters were generated. The optimum variables recommended by the software show an extraction temperature of 79.711°C, solid-liquid ratio of 1:5.22 g/mL, and extraction time of 26.13 mins. Validation of the model resulted in an anthocyanin content of 39.88 mg/L and phenolic content of 4.58 mg GAE/g extract, where both responses were in range of the predicted values confirming its validity. Incorporating a pre-treatment like steam blanching could substantially help in maximizing the extraction of both the desired compounds. Physicochemical tests like color and pH can also be done in order to determine its correlation with the responses. Lastly, since the study aims to achieve practical and commercial use of the extract as an additive, a thermal stability and comparison to industry standard can be done to further improve the framework of the stud